Influence of Strategy Implementation Practice on Organizational Performance of Ngos in Nairobi County - Leonard, Momos (Papanda Publisher, 2024)
Strategic implementation practices in the nonprofit sector are the same as in the for-profit sector. Some potential benefits that could be realized by a non-governmental organization (NGO) as a result of implementing strategic management practices include improved decision-making, enhanced organizational performance, greater clarity of purpose, and better alignment between the organization's activities and its goals. NGOs in Kenya are facing challenges as a result of the dynamic environment. This therefore calls for evaluation of strategic implementation practices and further implement. The study aimed to assess the influence of strategic implementation practices on the performance of NGOs in Nairobi County. Specifically the objective was to examine the influence of strategy implementation on the performance of Non-Governmental Organizations in Nairobi County. The study employed a descriptive research design. From the population of 1881 NGO registered in Nairobi County, a sample of 100 NGOs were selected using stratified random sampling technique to select strategic managers from each NGOs within Nairobi County to participate in the study. Primary data were collected using a combination of closed-ended and open-ended questionnaires. The data was then processed so that the responses could be classified into distinct sets. The information obtained was primarily quantitative. Descriptive statistics were used to analyze the data. The investigator was able to explain the data and quantify its utility thanks to descriptive statistical tools like SPSS and Microsoft Excel. The data was displayed visually in the form of tables and figures. The study outcome revealed an existing positive and significant correlation between Strategy Implementation Practice and the performance of NGOs in Nairobi County. This proves that, when Strategy Implementation Practice is enhanced, the performance of NGOs in Nairobi County also greatly improves. The study therefore recommended that, Managers in non-governmental organizations (NGOs) should improve their organizations' performance through strategic implementation practice if they focus on fostering a culture of shared vision, cooperation, and empowerment. The study also recommended that top executives learn more about the link between strategy implementation and strategic management techniques in order to boost the efficiency of NGOs in Nairobi County.